The Role of Digital Transformation in Enhancing Government Service Delivery in the UAE: A Literature Review - Alzaabi, Abdelaziz; Metawa, Noura; Marks, Adam (International Review of Management and Marketing, 2025)
This study aims to explore the role of digital transformation in augmenting government service delivery in the United Arab Emirates (UAE). In the Fourth Industrial Revolution context, the UAE proactive digital strategy, underpinned by Vision 2021, aims to leverage technologies like AI and IoT to transform public service delivery, enhance efficiency, and ensure transparency. The methodology of the study encompasses a systematic review of academic literature and secondary sources to discern trends, drivers, barriers, and the broader socio-economic implications of digital government initiatives. The paper organizes existing literature into five stages, from the evolution of eGovernment to the current digital government paradigm. It addresses the impact of digital innovations, the strategic deployment of digital infrastructure in developing smart cities, and the integration of advanced technologies in public administration. Findings indicate that the UAE has made significant progress in e-governance and is ranked highly globally. It has also identified persistent challenges such as digital literacy and the need for adaptive policy frameworks in response to technological advances. The study advocates for continuous innovation and the inclusion of best practices to bridge the digital divide and sustain UAE leadership in digital governance. It also provides a foundation for future empirical research to validate the effects of digital transformation on government service delivery in the UAE.